Diaspora remittance, financial system and sustainable economic development in Nigeria - Osayi Valentine Igbinedion; Akemieyefa Matthew (Journal of Management and Science, 2023)
The Study x-rayed diaspora remittance, the Nigerian financial system and sustainable economic development in Nigeria. The study used remittance inflows as measure of Diaspora Remittance and the Gross Domestic Product (GDP) as a measure of sustainable economic development. The study examined the absorptive capacity of the Nigerian financial system to mobilize diapora remittance and transform same into sustainable economic growth and development. Content Analysis (CA) technique was deployed to analyse and examine the data collected from the Central Bank of Nigeria (CBN) Statistical Bulletins for various years, Nigerian Bureau of Statistics (NBS) and the World Bank Development Indicators data base from 1987 to 2020. The data are comprised of the values of diaspora remittance, Gross Domestic product (GDP) and Official development Assistance (ODA). The analysis of the data revealed that the Nigerian financial system mobilized millions and billions of US dollars in remittance into the economy for the period which span thirty fours years with diaspora remittance reaching its peak of twenty six billion, eight hundred and ninety one million, nine hundred and eighty thousand two hundred dollars in 2011. Between 2011 and 2020, the Nigerian financial system raked in an average of twenty five billion US dollars in remittance inflows into the economy. Following from the foregoing findings, the study recommended that the Central Bank of Nigeria (CBN) being the monetary and regulatory authority of the banking system, should formulate policies that would further encourage the inflow of Diaspora remittance through the banking system such that diaspora remittances are well utilized to boost employment generation in order to engender sustainable economic growth and development.